Strategic communication as a key resource to achieve digital positioning: Case study. Centro de Apoyo en la Crianza y la Maternidad y Paternidad - Acunar - Jumbo Osorio, Hugo; Valdiviezo-Abad, Cesibel; Córdova Camacho, Jhoana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This article shows a quantitative analysis through two research instruments: web analytics and social network analytics applied to the Center for Parenting and Maternity and Paternity Support -Acunar-, an organization with online presence that focuses on providing advice and support to couples, pregnant women, fathers and mothers of families around the care of children. The main objective of the research was to investigate the communicational situation of Acunar digital environments and to deepen on the platforms used to generate communication with their various audiences.